Retinopathy of prematurity and neurodevelopmental outcomes in preterm infants: A systematic review and meta-analysis - Diggikar, Shivashankar; Gurumoorthy, Puvaneswari; Trif, Paula; Mudura, Diana; Nagesh, N. Karthik; Galis, Radu; Vinekar, Anand; Kramer, Boris W. (Frontiers in Pediatrics, 2023)
Background Retinopathy of Prematurity (ROP) and abnormal brain development share similar risk factors and mechanisms. There has been contrasting evidence on the association of ROP with adverse neurodevelopmental outcomes. Objective We analysed the association between ROP at levels of severity and treatment with all neurodevelopmental outcomes until adolescence. Data source We followed PRISMA guidelines and searched Medline and Embase from August 1st,1990 to March 31st, 2022. Study Selection and Participants Randomized or quasi-randomized clinical trials and observational studies on preterm infants (<37 weeks) with ROP (Type 1/severe ROP, Type 2/milder ROP, laser/anti-VEGF) were included. Data extraction and synthesis We included the studies on ROP and any neurocognitive or neuropsychiatric outcomes. Outcomes Primary outcomes: Cognitive Composite scores (CCS) evaluated between 18–48 months of age by BSID or equivalent Scale, Neurodevelopmental impairment (Moderate to severe NDI/Severe NDI), cerebral Palsy, cognitive impairment, and Neuropsychiatric/behavioural problems. Secondary outcomes: Motor and Language composite scores evaluated between 18-48 months by BSID or equivalent Scale, Motor/Language impairment, Moderate/Severe NDI as defined by the authors. Results In preterm infants ‘any ROP’ was associated with increased risk of Cognitive impairment/intellectual disability (n=83,506; OR:2.56; 95% CI:1.40-4.69, p=0.002), cerebral Palsy (n=3706; OR:2.26; 95%CI:1.72-2.96, p<0.001) behavioural/psychiatric problems (n=81,439; OR:2.45; 95%CI:1.03-5.83, p=0.04 ), NDI as defined by authors (n=1,930; OR:3.83;95%CI:1.61-9.12, p=0.002). Type 1/severe ROP increased the risk of CP (OR:2.19;95% CI:1.23-3.88, p=0.07) than Type 2 ROP at 18-24 months, cognitive impairment or intellectual disability (n=5,167; OR:3.56; 95%CI:2.6-4.86; p<0.001), behavioural/ psychiatric problems (n=5,500; OR:2.76; 95%CI:2.11-3.60, p<0.001). Infants treated with anti-VEGF have higher odds of moderate cognitive impairment than laser surgery group if adjusted data is analysed (aOR: 1.93; 95% CI:1.23-3.03, p=0.04) but not CP (aOR:1.29; 95% CI: 0.65-2.56, p=0.45). All outcomes were adjudged with ‘very low’ certainty of evidence. Conclusion and Relevance Infants with ‘any ROP’ had higher risks of cognitive impairment/intellectual disability, cerebral palsy, behavioural/psychiatric problems.Anti-VEGF treatment increased the risk of moderate cognitive impairment. These results support causation of ROP and anti-VEGF treatment with adverse neurodevelopmental outcomes.